HUBUNGAN DIETARY INFLAMMATORY INDEX (DII) DAN DIETARY ACID LOAD (DAL) DENGAN KEJADIAN OBESITAS - Sophia Rose; Selma Avianty; Dzul Fahmi Afriyanto (JOURNAL HEALTH AND NUTRITIONS, 2026)
Obesity is a global nutritional problem that continues to rise and serves as a major risk factor for non-communicable diseases. Dietary patterns that trigger inflammation and acid-base imbalance, measured by the Dietary Inflammatory Index (DII) and Dietary Acid Load (DAL), were suspected contribute to obesity. The study aimed to analyze the association between DII and DAL with obesity among employees at Universitas Kusuma Husada Surakarta. An observational study with a cross-sectional design was conducted involving 112 adult respondents (mean age 35 years) selected using a saturated sampling technique. Data were collected through interviews, anthropometric measurements (BMI, waist circumference, body fat, skeletal muscle), and SQ-FFQ questionnaires to calculate DII and DAL scores using Potential Renal Acid Load (PRAL) and Net Endogenous Acid Production (NEAP) methods. The association between variables was analyzed using Spearman’s rank correlation test (p<0.05). Results showed that 53.6% of respondents were classified as overweight or obese, with a mean DII score of -0.02 (anti-inflammatory category) and a mean PRAL score of 11.10 mEq/day, indicating that 83% had an acid-forming potential. No significant association was found between DII and anthropometric profiles, whereas DAL was significantly associated with subcutaneous fat (r=-0.204; p=0.031), skeletal muscle (r=0.242; p=0.01), and body fat percentage (r=-0.198; p=0.036). The conclusion indicated that there were significant association between DAL with body composition. These findings suggested that dietary acid load had a greater influence on body composition than dietary inflammatory potential. Obesitas merupakan masalah gizi global yang terus meningkat dan berperan sebagai faktor risiko utama penyakit tidak menular. Pola makan yang memicu inflamasi dan ketidakseimbangan asam-basa, yang diukur melalui Dietary Inflammatory Index (DII) dan Dietary Acid Load (DAL), diduga berkontribusi terhadap obesitas. Penelitian ini bertujuan menganalisis hubungan DII dan DAL dengan kejadian obesitas pada pegawai Universitas Kusuma Husada Surakarta. Penelitian observasional dengan desain cross-sectional ini melibatkan 112 responden dewasa dengan usia rata-rata 35 tahun yang dipilih dengan teknik sampling jenuh. Data dikumpulkan melalui wawancara, pengukuran antropometri dengan IMT, lingkar pinggang, lemak tubuh, otot skeletal, serta kuesioner SQ-FFQ untuk menghitung skor DII dan DAL menggunakan metode Potential Renal Acid Load (PRAL) dan Net Endogenous Acid Production (NEAP). Analisis hubungan variabel dilakukan dengan uji Rank Spearman (p<0,05). Hasil menunjukkan 53,6% responden memiliki status gizi gemuk, dengan rerata skor DII -0,02 pada kategori anti-inflamasi dan skor PRAL 11,10 mEq/hari yang menunjukkan berpotensi membentuk asam sebanyak 83%. Tidak ditemukan hubungan signifikan antara DII dan profil antropometri, sedangkan DAL berhubungan signifikan dengan lemak subkutan (r=-0,204; p=0,031), otot skeletal (r=0,242; p=0,01), dan persen lemak (r=-0,198; p=0,036). Kesimpulan penelitian menunjukkan terdapat hubungan signifikan antara DAL dengan komposisi tubuh. Hasil penelitian ini menunjukkan bahwa beban asam diet lebih mempengaruhi komposisi tubuh dibandingkan potensi inflamasi diet.